The Institutional Cost of Acquiring 100 mL of Human Milk for Very Low Birth Weight Infants in the Neonatal Intensive Care Unit. (August 2013) - Jegier, Briana J.; Johnson, Tricia J.; Engstrom, Janet L.; Patel, Aloka L.; Loera, Fabiola; Meier, Paula
Background: Human milk from the biologic mother (HM) reduces disease burden and associated costs of care during and after neonatal intensive care unit (NICU) hospitalization for very low birth weight (VLBW; birth weight < 1500 g) infants, when compared to feedings of donor human milk (DHM) or commercial formula (CF). However, compared to DHM and CF, little is known about the institutional cost to acquire HM from the biologic mother. Objective: This study aimed to determine the institutional cost of acquiring HM for VLBW infant feedings during the NICU hospitalization. Methods: This analysis examined 157 maternal pumping records from a prospective cohort study evaluating health outcomes and cost of HM feedings for VLBW infants. The costs for the breast pump rental fee, 1-time pump kit purchase, and disposable food-grade containers for storing expressed HM were evaluated using standard cost analysis techniques. Results: The median cost of acquiring 100 mL of HM varied from 0.51 when mothers pumped ≥ 700 mL daily to 7.93 for those who pumped < 100 mL daily. Mothers who pumped ≥ 100 mL daily had lower acquisition cost compared to both DHM (14.84/100 mL) and CF (3.18/100 mL). For mothers who pumped > 100 mL daily, the exact day of pumping where the cost of HM was less expensive than DHM or CF was 4 to 7 days and 6 to 19 days, respectively. Conclusion: Human milk from the biologic mother has lower acquisition cost than DHM and CF when mothers provided ≥ 100 mL daily and pumped for a sufficient number of days (range, 4-19). Neonatal intensive care units should prioritize resources to ensure that mothers achieve this daily milk volume.